PERSEPSI MAHASISWA ANGKATAN 2021 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU TERHADAP PODCAST SAKURA TIPS SEBAGAI MEDIA AJAR TAMBAHAN PEMBELAJARAN MENYIMAK TINGKAT DASAR - Nigmatullin, Rizky; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study is a quantitative research analyzed using statistical anddescriptive methods. The aim of this research is to describe the perceptions of studentsin the Japanese Language Education program at Riau University towards the SakuraTips Podcast as a medium for basic listening learning. The data collection techniqueused in this research is a questionnaire. The sample consists of 16 students from the2021 cohort. Data analysis techniques include statistical and descriptive analysis of thequestionnaire results. The validity analysis of the questionnaire shows that out of 17questions, 13 are valid. The reliability test of the instrument also shows good results,with a reliability coefficient of 0.991, indicating high reliability. Overall, the results ofthis study indicate that the Sakura Tips Podcast has a positive impact on basic listeninglearning in the classroom.Key Words: Media, Podcast, Listening Learning